(3GdVhA GddGeY dCgd GdbQf GdJGSYs - (3TeS GdOjf eMeO Hf YHO GdQMje GdSNGhis; (3GdfSGFj , CMeO Hf Ydj Hf TYjH Hf Ydj Hf SfGf Hf HMQ Hf OjfGQ GdfSGFj, CHh YHO GdQMef,J (B303 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGeY GdTJGJ , hQGaY ef TGA ai GdMjGI hHYO GdeeGJ s
(3BNQgG (B:s
(3jfJgi Edi ef CSeg (B: (3YHO GdSdGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B244s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B96 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs